A system for free-air ozone concentration elevation with rice and wheat: Control performance and ozone exposure regime - Tang, Haoye; Liu, Gang; Han, Yong; Zhu, Jianguo; Kobayashi, Kazuhiko (Atmospheric environment (1994), 2011)
A system for free-air concentration enrichment with ozone (FACE-O 3) was installed in a field in Jiangsu Province of China to grow wheat and rice plants in either ambient [O 3] (A-O 3) or elevated [O 3] (E-O 3) without any enclosures. Ozone generated from pure O 2 and mixed with compressed air was released into the E-O 3 plots from a 14 m diameter octagon. The gas release was controlled for each E-O 3 plot with an algorithm based on wind direction, wind speed and [O 3] at the center of the plot. With 1-min mean [O 3], the achieved elevation was within ±20% of the target, which is 50% above A-O 3, for 94% of time, and within ±10% of the target for 73% of time on average across 4 years from 2007 to 2010. Ozone fumigation ran on daytime, but was withheld when ambient [O 3] was below 20 ppb or leaves were wet. The discontinuity in O 3 release resulted in the daily mean 7 h [O 3] (M7, 900–1600 h Chinese Standard Time) in E-O 3 by only 24% higher than that in A-O 3. The average effective increase in AOT40 (accumulated [O 3] above the threshold of 40 ppb) was 115%. Ozone exposure regime in E-O 3 as characterized by M7 and AOT40 was compared with that in a scaled-up [O 3] (S-O 3), which was obtained by scaling A-O 3 by 1.24: the ratio of M7 in E-O 3 to that in A-O 3. For the same M7, E-O 3 had higher AOT40 than S-O 3, because E-O 3 had more high [O 3] peaks than S-O 3. The shift in AOT40 is only modest, however, and the [O 3] regime in E-O 3 was consistent with that in open-top chamber experiments in the past. This FACE-O 3 system can thus maintain elevated [O 3] in open field with modest alteration to [O 3] regime to an extent comparable to open-top chambers. ► We examined control performance and O 3 concentration regime in a FACE-ozone system. ► Control performance was comparable to or better than that in other systems. ► O 3 concentration regime in FACE-ozone system was peakier than that in ambient air. ► The change in O 3 regime could introduce small bias in crop yield loss estimation.